Synthesis and characterization of phosphonated polybenzimidazole membranes with improved proton conductivity for high-temperature proton exchange membrane applications. (November 2022) - He, Yueming; Wang, Meng; Chen, Hongzhou; Peng, Xiaohong
The study has synthesized a novel dicarboxylic acid monomer with phosphonate group, 2-((diethoxyphosphoryl)methyl)-[1, 1 ′ -biphenyl]-4, 4 ′ -dicarboxylic acid (PMDA), and then successfully prepared a series of polybenzimidazole polymers containing methyl-phosphonic acid group and ether group (POPBI-x) via the polycondensation between PMDA, 4, 4 ′ -oxybis (benzoic acid) (OBBA) and 3, 3 ′ -diaminobenzidine (DAB) in polyphosphoric acid (PPA)/phosphorus pentoxide (P2 O5 ). Meanwhile, the smooth membranes were fabricated via the solution-casting method. Results of TGA, the Fenton's reagent immersing test, and the tensile test showed that the POPBI-x membranes possessed good thermo-oxidative stability and mechanical properties. Moreover, compared to poly[2, 2 ′ -(p-oxydiphenylene)-5, 5 ′ -benzimidazole] (OPBI), POPBI-x had a significant enhancement in the phosphoric acid doping level, PA retention ability, and proton conductivity after doped with phosphoric acid (PA) because the methyl-phosphonic acid groups on the backbones enriched the hydrogen bonding interactions between the polymer chain and phosphoric acid. Notably, the POPBI-19 exhibited a high phosphoric acid doping level of approximately 11.3 and excellent proton conductivity of approximately 0.0523 S cm −1 at 180°C under anhydrous conditions.